Production of gamma aminobutyric acid (GABA)- Miso using Candida parapsilosis Isolated from a commercial soy sauce moromi - Chong, Shin Yee; Zul Ilham,; Nurul Aqilah Mohd Zaini,; Muhamad Hafiz Abd Rahim,; Siva Raseetha,; Raposo, António; Alarifi, Sehad N.; Mohd Nizam Lani,; Wan Abd Al Qadr Imad Wan-Mohtar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A newly identified yeast, Candida parapsilosis strain KBC (CPSKBC) was tested for its GABA-producing potential in miso fermentation and consumer acceptability towards the GABA-miso was evaluated through sensory analysis. Three different formulations were used over one month to make the GABA-miso: formulation 1 (F1) used soybeans, rice koji, and miso starter; formulation 2 (F2) used soybeans, rice koji, and CPSKBC suspension; and formula 3 (F3) used soybeans, rice koji, miso starter, and CPSKBC suspension. High Performance Liquid Chromatography (HPLC) was used to measure the gamma-aminobutyric acid (GABA) concentration of the miso produced. F3 produced the highest GABA (36.73 mg/L), followed by F2 (34.54 mg/L) and F1 (28.42 mg/L). Sensory evaluation was conducted with 60 panelists using a 9-point hedonic scale. For all the sensory attributes evaluated (appearance, color, odor, taste and overall acceptability), the results showed no significant differences (p >0.05) between groups of miso (F1, F2, and F3) and commercial miso (C1). We can conclude that our products (F1, F2, and F3) matched with commercially produced miso in the market. This study demonstrated that CPSKBC was able to produce GABA-miso (F2 and F3) which is acceptable to the consumer.